Fast forward your career a personal playbook to boost leadership - Lureti, Simonetta; Furlani, Lucio (Business Expert Press, 2021)
Fast Forward Your Career is for managers, corporate staff, and MBA students who want to position themselves for their next career opportunity and learn the necessary skills to be successful in the digital age. In this book, the authors provide a useful, practical, and intuitive guide to important topics, often mentioned, not always known, but fundamental to develop your leadership skills and guide your career in the digital age. They have condensed their experience as executives, coaches, consultants to challenge you with insights and further application. The book combines practical concepts with storytelling to let you observe skills in practice.